Gender and food systems in Kenya: A case study of the poultry value chain in eastern Kenya - Bukashi, Salome A.; Ngutu, Mariah; Omia, Dalmas O.; Musyoka, Mercy M.; Chemuliti, Judith K.; Nyamongo, Isaac K. (International Food Policy Research Institute, 2023)
Women are key stakeholders in sustainable and resilient food systems, given their roles as primary food producers and household caretakers (Visser and Wangu 2021). Understanding how gendered roles affect food security and women’s well-being is essential for pursuing sustainable development (Angel-Urdinola and Wodon 2010; Doss, Meinzen-Dick, and Quisumbing 2018; Meinzen-Dick et al. 2019). Their participation in agriculture is documented widely, but there is a need for more gendered data on the roles of men and women in different contexts and agricultural value chains, including livestock value chains (Micere Njuki et al. 2016; Richardson 2018; Doss and Rubin 2021; Njuki et al. 2021). This file also includes the introduction to Part Five.